The imperial cult in the Latin West. studies in the ruler cult of the western provinces of the Roman Empire - Fishwick, Duncan, 1929- (Religions in the Graeco-Roman World, 2002)
This volume analyzes the priesthood of the provincial cult in every province of the Latin west where evidence has survived in the period from Augustus down to the mid third century. Particular attention is paid to the epigraphic record, notably the Testimony of honorific statues especially at provincial centres, but discussion also focusses on the origin and background of provincial priests, their office and duties, and their careers both before and after holding provincial office. Of special interest are the sixteen tables that list the main facts preserved by the epigraphic record, also a concluding overview that summarizes the principal features of the institution including the office of priestess and the role of administrative officials. Some fifty plates illustrate the text.